2000
DOI: 10.4049/jimmunol.165.6.3250
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressant FTY720 Induces Apoptosis by Direct Induction of Permeability Transition and Release of Cytochrome c from Mitochondria

Abstract: FTY720 has immunosuppressive activity in experimental organ transplantation and shows a prompt and protracted decrease of blood T lymphocytes upon oral administration. The blood lymphocyte decrease in vivo was mainly a result of FTY720-induced apoptosis. However, this apoptotic mechanism is not well understood. We examined the mechanism of FTY720-induced apoptosis in lymphoma. Western blotting and fluorescent caspase-specific substrate revealed that caspase-3 is involved in FTY720-induced apoptosis, whereas ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 61 publications
5
67
1
Order By: Relevance
“…6A, p27 in HL-60RG and both types of Jurkat cells was increased during 2-3 h of treatment with FTY720, but the p21 level in both types of Jurkat cells was not increased, and in fact decreased after 6 h of treatment with FTY720. This may have been the result of caspase-3-mediated cleavage, since FTY720 has been shown to activate caspase-3 within 3 h. 25,28) We could not detect p21 in HL-60RG cells, in agreement with the previous report. 29) Further confirmation of the FTY720-induced p27 increase to CDKs kinase activity was sought.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…6A, p27 in HL-60RG and both types of Jurkat cells was increased during 2-3 h of treatment with FTY720, but the p21 level in both types of Jurkat cells was not increased, and in fact decreased after 6 h of treatment with FTY720. This may have been the result of caspase-3-mediated cleavage, since FTY720 has been shown to activate caspase-3 within 3 h. 25,28) We could not detect p21 in HL-60RG cells, in agreement with the previous report. 29) Further confirmation of the FTY720-induced p27 increase to CDKs kinase activity was sought.…”
Section: Resultssupporting
confidence: 81%
“…This can be explained by our previous finding that FTY720 perturbs mitochondria directly and thereby initiates the process of apoptosis. 25) In the present study, however, particularly after early incubation with FTY720 (2-3 h), cell death occurred specifically in the G0/G1 phase, and G2/M phase cells seemed to be protected against the action of FTY720. It has been demonstrated that Bcl-2 protein can be phosphorylated, resulting in a change of its function.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Most studies on mitochondrial involvement in cell death have been performed on drug-induced models of apoptosis [22], and the association between mitochondrial alterations and infection has only recently been explored. It has been shown that Pseudomonas aeruginosa induces apoptosis by a JKN-and also by a Dc m -dependent mechanism [23].…”
Section: Introductionmentioning
confidence: 99%
“…We used anti-Fas antibody as a model inducer of receptor-mediated apoptosis, and FTY720 for mitochondria-mediated apoptosis. FTY720 directly perturbs the mitochondrial membrane potential pore to decrease DW m and release cytochrome c, leading to caspase activation and DNA fragmentation (19).…”
mentioning
confidence: 99%